The NATO Response Force: A qualified failure no more?. Issue 3 (2nd September 2017) - Ringsmose, Jens; Rynning, Sten
ABSTRACT: With much fanfare, NATO declared its rapid reaction force—the NATO Response Force (NRF)—an Initial Operational Capability in 2004. This article addresses four questions: Where did the NRF come from? What does it look like in 2017? What have been the major obstacles for the NRF fulfilling its promises? And where is the NRF likely to go? The article holds two main arguments. First, due to inadequate fill-rates and disagreements as to the force's operational role, the NRF was for many years a "qualified failure." The force failed to become the operational tool envisioned by the allies in 2002. While not without effect, it fell hostage to the harsh reality of the expeditionary wars of Iraq and Afghanistan. Second, the NRF is off to a fresh beginning and will likely be considered at least a partial success by the allies in the years to come.